Orbit characteristics of the tristatic EISCAT UHF meteors - Szasz, C.; Kero, J.; Meisel, D. D.; Pellinen-Wannberg, A.; Wannberg, G.; Westman, A. (Monthly Notices of the Royal Astronomical Society, 2008)
The tristatic EISCAT 930-MHz UHF system is used to determine the absolute geocentric velocities of meteors detected with all three receivers simultaneously at 96 km, the height of the common radar volume. The data used in this study were taken between 2002 and 2005, during four 24-h runs at summer/winter solstice and vernal/autumnal equinox to observe the largest seasonal difference. The observed velocities of 410 tristatic meteors are integrated back through the Earth atmosphere to find their atmospheric entry velocities using an ablation model. Orbit calculations are performed by taking zenith attraction, Earth rotation as well as obliquity of the ecliptic into account. The results are presented in the form of different orbital characteristics. None of the observed meteors appears to be of extrasolar or asteroidal origin; comets, particularly short-period (<200 yr) ones, may be the dominant source for the particles observed. About 40 per cent of the radiants can be associated with the north apex sporadic meteor source and 58 per cent of the orbits are retrograde. There is evidence of resonance gaps at semimajor axis values corresponding to commensurabilities with Jupiter, which may be the first convincing evidence of Jupiter's gravitational influence on the population of small sporadic meteoroids surveyed by radar. The geocentric velocity distribution is bimodal with a prograde population centred around 38 km s−1 and a retrograde population peaking at 59 km s−1. The EISCAT radar system is located close to the Arctic Circle, which means that the North Ecliptic Pole (NEP) is near zenith once every 24 h, i.e. during each observational period. In this particular geometry, the local horizon coincides with the ecliptic plane. The meteoroid influx should therefore be directly comparable throughout the year.